Air Pollution Effects to the Subtype and Severity of Lung Cancers - Lee, Hung-Chi; Lu, Yueh-Hsun; Huang, Yen-Lin; Huang, Shih Li; Chuang, Hsiao-Chi (Frontiers in Medicine, 2022)
The correlation between lung cancer incidence and air pollution had been established in previous researches, but the other detail impact of air pollution to lung cancer was still under investigation. This study aimed to explore if air pollution affected the subtype and staging of lung cancer. At the same time, we investigated the effect of individual pollutant to subtypes and staging. Single center data were extracted from January 1, 2020 to June 30, 2020 using the Searching engine in radiology reporting system of Shuang-Ho Hospital, New Taipei City, Taiwan. 169 patients were finally included for analysis. The national wide statistic data of lung cancer were extracted from Taiwan Cancer Registry. The air quality data were extracted from Taiwan air quality monitoring network. Comparison of the single center lung cancer characteristics with national wide data was made using chi-square test. Comparison of the air quality of the living place of the included cases with the average quality in Taiwan in 2020 was made using Z-test. The result shows there was significant difference of cancer subtype and staging between the regional data and the national wide data. The regional data demonstrated a tendency of higher incidence of adenocarcinoma and advanced stage disease. As for air quality, there was no significant difference. The regional PM10 level presented generally lower level in regional data as comparing to Taiwan in 2020 with near statistically significance P-value (0.052); the regional NO2 level presented generally higher level in regional data as comparing to Taiwan in 2020 with near statistically significance P-value (0.060). The results indicate that air pollution might be related to increase adenocarcinoma ratio and advanced stage of lung cancer at initial presentation. The NO2 was probably the leading pollutant causing this trend.